A Generalized Quantity Discount Pricing Model to Increase Supplier's Profits - Lee, Hau L.; Rosenblatt, Meir J. (Management Science, 1986)
In this paper, the joint problem of ordering and offering price discount by a supplier to his sole/major buyer is analyzed. The objective is to induce the buyer to alter his order schedule and size so that the supplier can benefit from lower set up, ordering, and inventory holding costs. We generalize the quantity discount pricing model of Monahan (Monahan, J. P. 1984. A quantity discount pricing model to increase vendor profits. Management Sci. 30 (6) 720–726.) to: (1) explicitly incorporate constraints imposed on the amount of discount that can be offered; and (2) relax the implicit assumption of a lot-for-lot (or order-for-order) policy adopted by the supplier. An algorithm is developed to solve the supplier's joint ordering and price discount problem.